Reflective Practice in EFL Teacher Professional Development:: Barriers, Strategies, and Growth - Susanti, Desi; Siti Rodliyah, Rojab; Sri Lengkanawati, Nenden (Universitas Jambi, Magister Program of English Education Department, 2026)
This study investigates the role of reflective practice in empowering English language teachers toward sustained professional development. Despite its recognized importance, many in service teachers struggle to integrate reflective routines into their daily practice due to systemic and personal constraints. Using a qualitative design, data were collected from eight postgraduate English education students at Universitas Pendidikan Indonesia through open-ended questionnaires. Responses were analysed using Braun and Clarke’s (2006) thematic analysis framework. Findings reveal five interconnected barriers: time constraints arising from heavy institutional workloads, limited access to reflective resources and tools, insufficient collaborative culture within schools, methodological uncertainty in selecting appropriate reflection strategies, and sceptical attitudes toward the value of reflection. These challenges are contextually shaped by individual, institutional, and cultural factors. The theoretical contribution of this study lies in its application of Schön’s (1983) reflective practitioner framework and Farrell’s (2015) reflective practice model to an underexplored Indonesian EFL context, offering a contextualized mapping of barriers that extends existing local research. The study suggests that effective support for reflective practice requires both structured institutional frameworks and the embedding of reflective competencies as a core outcome in teacher education programmes. When adequately supported, reflective practice may foster critical pedagogical awareness and a professional disposition oriented toward continuous improvement.